Evaluating the longitudinal risk of social vigilance on atherosclerosis: study protocol for the North Texas Heart Study. Issue 8 (14th August 2017) - Ruiz, John M; Taylor, Daniel J; Uchino, Bert N; Smith, Timothy W; Allison, Matthew; Ahn, Chul; Johnson, Jillian J; Smyth, Joshua M
Abstract : Introduction: Psychosocial factors are increasingly recognised as important determinants of cardiovascular disease risk. The North Texas Heart Study aims to understand the mechanisms responsible for this association with a focus on social vigilance (ie, scanning the environment for social threats). There is also growing interest in supplementing traditional methods (eg, survey assessment of psychosocial risk paired with cross-sectional and longitudinal health outcomes) with daily or repeated momentary assessment of psychosocial factors. However, there are relatively few longitudinal studies directly comparing these approaches with hard endpoints. Methods and analysis: The North Texas Heart Study proposes a longitudinal measurement burst design to examine psychosocial determinants of subclinical atherosclerosis. A sample of 300 healthy community participants, stratified by age and gender, will complete survey measures, as well as 2 days of ecological momentary assessment at baseline and at a 2-year follow-up. A range of psychosocial and behavioural factors, objective biomarkers, as well as carotid intima-media thickness (cIMT) will be assessed at both time points. Unadjusted and adjusted models will evaluate cross-sectional associations and determinants of change in the cIMT. Ethics and dissemination: The Institutional Review Board at the study coordinating institute (University of North Texas) has approved this study. Positive, negative or inconclusive primary and ancillary findings will be disseminated in scientific journals and conferences.